Effect of ventilation in enclosure machine system on MWF aerosol properties - Sokolović Dunja S.; Höflinger Wilhelm; Zavargo Zoltan Z.; Šećerov-Sokolović Radmila M. (Hemijska Industrija, 2012)
In this paper the influence of ventilation air velocity on properties of metal working fluids (MWF) aerosol/mist is presented. Aerosol characteristics were monitored in the chamber as well as at the entrance of ventilation pipe by optical particle size analyzer. Aerosol was generated from 6% water emulsion of three commercial MWF. Four different velocities, less than the velocity of secondary atomization, were examined (1, 3, 6, 8 m/s). Droplets size distribution, mass concentration (mg/m3), as well as number concentration (P/cm3) were measured and analyzed. From the results obtained it may be seen that coalescence is more pronounced as the velocity increases, although the number concentration decreases, due to higher air dilution. Therefore, more droplets are in a whirling motion at higher air velocities, hence more random collisions are possible. Further analysis shows that there is one value of air velocity under which the maximum difference between the aerosol in chamber and the aerosol at the entrance of the pipe can be observed. This velocity could be named specific velocity and depends on the given aerosol properties. It could be assumed that specific velocity is conditioned by the properties of oil from which emulsion is prepared. Oil viscosity and molar mass have greatest influence on the specific velocity.